Experimental Study of Replacement the Tension Reinforcing Bars in Concrete Beams by Steel Pipes - Saadoon Al-Yassri, Labeeb; Mahdi Al-Khekany, Alaa; Satea Abbas, Hajer (International Journal of Engineering and Technology, 2018)
Structures designed with reinforced concrete beams are used extensively in construction projects because of their functional and economic features. In this research, tested concrete beams were cast and reinforced with small diameter steel pipes and /or steel bars as flexural reinforcement to study the effect of this configuration of reinforcement on the structural behavior of reinforced concrete beams. The idea of this research involves performing and testing of four reinforced concrete beams reinforced by small diameter steel pipes with different percentages of replacement with traditional steel bars (0%, 33%, 66% and 100%). The experimental results showed that using of steel pipes reduces the flexural capacity by (2.7, 18.3, 37.5%) if compared with traditional steel bar according to the replacement percentages of (33%, 66%, and 100%) respectively. Moreover, the stiffness of beams reinforced with steel pipes (fully or partially) decreased as a result of the difference in the mechanical properties between steel bar and the steel pipe and also, the bond strength reduction between the smooth steel pipe and surrounded concrete.Â Â
Keywords: Reinforced concrete beam; steel pipes; steel bars; flexural strength; mode of failure